The impact of critical event checklists on medical management and teamwork during simulated crises in a surgical daycare facility3. (2nd November 2016) - Everett, T. C.; Morgan, P. J.; Brydges, R.; Kurrek, M.; Tregunno, D.; Cunningham, L.; Chan, A.; Forde, D.; Tarshis, J.
Summary: Although the incidence of major adverse events in surgical daycare centres is low, these critical events may not be managed optimally due to the absence of resources that exist in larger hospitals. We aimed to study the impact of operating theatre critical event checklists on medical management and teamwork during whole‐team operating theatre crisis simulations staged in a surgical daycare facility. We studied 56 simulation encounters (without and with a checklist available) divided between an initial session and then a retention session several months later. Medical management and teamwork were quantified via percentage adherence to key processes and the Team Emergency Assessment Measure, respectively. In the initial session, medical management was not improved by the presence of a checklist (56% without checklist vs. 62% with checklist; p = 0.50). In the retention session, teams performed significantly worse without the checklists (36% without checklist vs. 60% with checklist; p = 0.04). We did not observe a change in non‐technical skills in the presence of a checklist in either the initial or retention sessions (68% without checklist vs. 69% with checklist (p = 0.94) and 69% without checklist vs. 65% with checklist (p = 0.36), respectively). Critical events checklists do not improve medical management or teamwork during simulated operating theatre crises in an ambulatory surgical daycare setting.